Are Mobile Persons With Parkinson Disease Necessarily More Active?. Issue 4 (3rd October 2021) - Zajac, Jenna A.; Cavanaugh, James T.; Baker, Teresa; Colón-Semenza, Cristina; DeAngelis, Tamara R.; Duncan, Ryan P.; Fulford, Daniel; LaValley, Michael; Nordahl, Timothy; Rawson, Kerri S.; Saint-Hilaire, Marie; Thomas, Cathi A.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Purpose: Walking activity in persons with Parkinson disease (PD) is important for preventing functional decline. The contribution of walking activity to home and community mobility in PD is poorly understood. Methods: Cross-sectional baseline data (N = 69) were analyzed from a randomized controlled PD trial. The Life-Space Assessment (LSA) quantified the extent, frequency, and independence across 5 expanding levels of home and community mobility, producing individual subscores and a total score. Two additional summed scores were used to represent mobility within (Levels 1-3) and beyond (Levels 4-5) neighborhood limits. An accelerometer measured walking activity for 7 days. Regression and correlation analyses evaluated relationships between daily steps and mobility scores. Mann-Whitney U tests secondarily compared differences in mobility scores between the active and sedentary groups. Results: Walking activity contributed significantly to the summed Level 1-3 score (β = 0.001, P = 0.004) but not to the summed Level 4-5 (β = 0.001, P = 0.33) or total (β = 0.002, P = 0.07) scores. Walking activity was significantly related to Level 1 (ρ = 0.336, P = 0.005), Level 2 (ρ = 0.307, P = 0.010), and Level 3 (ρ = 0.314, P = 0.009) subscores. Only the summed Level 1-3 score ( P = 0.030) was significantly different between the active and sedentary groups. Discussion and Conclusions: Persons with PD who demonstrated greater mobility beyond the neighborhood were not necessarily more active; walking activity contributed more so to home and neighborhood mobility. Compared with LSA total score, the Level 1-3 summed score may be a more useful participation-level measure for assessing the impact of changes in walking activity. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1 available at: http://links.lww.com/JNPT/A349 )